Pathophysiology, Treatment and Management of Obesity - Meena, Kedar Prasad; Samal, Pradeep Kumar (Perspective of Recent Advances in Medical Research Vol. 1, 2022)
Obesity continues be among the top health concerns across the globe. Despite our failure to contain the high prevalence of obesity, we now have a better understanding of its pathophysiology, and how excess adiposity leads to type 2 diabetes, hypertension, and cardiovascular disease. Some medications play significant role in weight gain such as diabetic treatments, steroid hormones, psychotropic medications, antihypertensive drugs, contraceptives, protease inhibitors and antihistamines. The corticolimbic system consisting of large cortical areas, basal ganglia, hippocampus and amygdale is intimately connected to the hypothalamus and brain stem. And provide the emotional cognitive and executive support for ingestive behavior. The experimental design is selected according to the desirability to obtain the efficient and precise results. According to the selected statistical approach the relationship between the independent and the dependent variables is established.